Child Welfare System Involvement Among Children With Medical Complexity. (May 2022) - Azzopardi, Corry; Cohen, Eyal; Pépin, Karine; Netten, Kathy; Birken, Catherine; Madigan, Sheri
Children with medical complexity may be at elevated risk of experiencing child maltreatment and child welfare system involvement, though empirical data are limited. This study examined the extent of child welfare system involvement among children with medical complexity and investigated associated health and social factors. A retrospective chart review of children with medical complexity (N = 208) followed at a pediatric hospital-based complex care program in Canada was conducted. Descriptive statistics and odds ratios using logistic regression were computed. Results showed that nearly one-quarter (23.6%) had documented contact with the child welfare system, most commonly for neglect; of those, more than one-third (38.8%) were placed in care. Caregiver reported history of mental health problems (aOR = 3.19, 95%CI = 1.55–6.56), chronic medical conditions (aOR = 2.86, 95%CI = 1.09–7.47), and interpersonal violence or trauma (aOR = 17.58, 95%CI = 5.43–56.98) were associated with increased likelihood of child welfare system involvement, while caregiver married/common-law relationship status (aOR = 0.35, 95%CI = 0.16–0.74) and higher number of medical technology supports (aOR = 0.75, 95%CI = 0.57–0.99) were associated with decreased likelihood. Implications for intervention and prevention of maltreatment in children with high healthcare needs are discussed.